2022
DOI: 10.1158/0008-5472.can-22-0507
|View full text |Cite
|
Sign up to set email alerts
|

β2-Microglobulin Maintains Glioblastoma Stem Cells and Induces M2-like Polarization of Tumor-Associated Macrophages

Abstract: Glioblastoma (GBM) is a complex ecosystem that includes a heterogeneous tumor population and the tumor immune microenvironment (TIME), prominently containing tumor-associated macrophages (TAMs) and microglia. Here, we demonstrated that β2-microglobulin (B2M), a subunit of the class I major histocompatibility complex (MHC-I), promotes maintenance of stem-like neoplastic populations and reprograms the TIME to an anti-inflammatory, tumor-promoting state. B2M activated PI3K/AKT/mTOR signaling by interacting with P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…We found that porcine M2_IL4 + IL10 highly expressed PPARG , NTRK1 , ADIPOQ , FLT1 , HMOX1 , and M2_M-CSF highly expressed IL6 , CD4 , IGF1 , IL10 , PTGS2 , FOS , PPARG [ 50 , 51 , 52 ]. PPARG has an anti-inflammatory effect, and its ligand is responsible for clearing the expression of genes of apoptotic cells and macrophage-mediated inflammatory responses [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that porcine M2_IL4 + IL10 highly expressed PPARG , NTRK1 , ADIPOQ , FLT1 , HMOX1 , and M2_M-CSF highly expressed IL6 , CD4 , IGF1 , IL10 , PTGS2 , FOS , PPARG [ 50 , 51 , 52 ]. PPARG has an anti-inflammatory effect, and its ligand is responsible for clearing the expression of genes of apoptotic cells and macrophage-mediated inflammatory responses [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data suggest that B2M is involved in a wide range of physiological and pathological functions, such as cell proliferation and apoptosis, and is also regarded as an important prognostic factor and predictor of survival associated with multiple cancers. B2M activates the PI3K/AKT/mTOR signaling pathway by promoting secretion of transforming growth factor-β1 (TGFβ1) ( 26 ). The CRISPR-Cas9 system was used to develop CAR T cells with three types of gene editing, including that in the B2M.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, GAMs have been shown to play a role in promoting GSCs ( 119 122 ). Research by Wang et al.…”
Section: Interaction Between Gams and Gbm Cellsmentioning
confidence: 99%
“…Conversely, GAMs have been shown to play a role in promoting GSCs (119)(120)(121)(122). Research by Wang et al demonstrated that IL-6, which is secreted by microglia, can function as a growth factor for GSCs and enhance their biological function (122).…”
Section: Interactions Between Gams and Gscsmentioning
confidence: 99%